Convenção de arbitragem - Vidal, Gustavo Pane (2016)
The Arbitration Law (Law no. 9,307/96) has promoted important innovations to the Institute, which has impelled its use for the solution of controversies. Prior to such a diploma, only arbitral commitments would set the arbitral tribunal. This manuscript reports on the analysis of the arbitration clause and the arbitral commitment, i.e., species of the arbitral agreement, through which parties solve their disputes according to the arbitral jurisdiction. The arbitrability of the litigation will be analyzed, so that a possible arbitration agreement can be established in some branches of Law. The manuscript also addresses the transmission, extension and extinction of the arbitration agreement